Morphometric study of the root anatomy in furcation area of mandibular first molars - Marcaccini, Andréa Marcia [UNESP]; Pavanelo, Ângela; Nogueira, Andressa Vilas Boas [UNESP]; de Souza, Joa̧o Antonio Chaves [UNESP]; Porciúncula, Hélio Ferraz [UNESP]; Cirelli, Joni Augusto [UNESP] (FapUNIFESP (SciELO), 2012)
Furcation involvement in periodontal disease has been a challenge for the dentist. Objective: The aim of this study was to investigate root dimensions in the furcation area of 233 mandibular first molars. Material and Methods: Digital photomicrographs were used to obtain the following measurements on the buccal and lingual surfaces of each tooth: root trunk height (RT), horizontal interadicular distance obtained 1 mm (D1) and 2 mm (D2) below the fornix and interadicular angle (IA). Results: Mean± standard deviation of buccal and lingual furcation measurements were, respectively, 1.37±0.78 mm and 2.04±0.89 mm for RT; 0.86±0.39 mm and 0.71±0.42 mm for D1; 1.50±0.48 mm and 1.38±0.48 mm for D2; 41.68±13.20° and 37.78±13.18° for IA. Statistically significant differences were found between all measured parameters for buccal and lingual sides (p<0.05, paired t test). Conclusions: In conclusion, the lingual furcation of mandibular first molars presented narrower entrance and longer root trunk than the buccal furcation, suggesting more limitation for instrumentation and worse prognosis to lingual furcation involvements in comparison to buccal lesions.
Keywords: Furcation defects; Periodontics; Tooth root